PENGARUH BAHAN PENGISI ORGANO-PRECIPITATED CALCIUM CARBONATE DALAM CAMPURAN PLA/LLDPE DENGAN ADANYA KOMPATIBILISER DITINJAU DARI SIFAT MEKANIK DAN FISIK - Melinda Sela; Ahmad Hafizullah Ritonga (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
The poor compatibility between Polylactic Acid (PLA) and Linear Low-Density Polyethylene (LLDPE), which has a different polarity, has decreased its mechanical and physical properties. Availability of Linear Low-Density Polyethylene grafting Oleic Acid (LLDPE-g-OA) compatibilizer and Organo-Precipitated Calcium Carbonate (O-PCC) filler in the PLA/LLDPE blends can improve the quality of the mechanical and physical properties of the polymer blends. This study aims to determine the influence of O-PCC as filler in the PLA/LLDPE blends with the existence of the LLDPE-g-AO compatibilizer to improve its mechanical and physical properties and compare the results with Precipitated Calcium Carbonate (PCC) filler. This polymer composite was made via a blending method with a solvent system, where PLA was dissolved in chloroform while LLDPE and LLDPE-g-AO were dissolved in xylene. After they were dissolved, glycerol 1% was added, followed by the addition of O-PCC variations. This research shows that the higher the filler concentration, the lower the water absorption percentage, where the optimum results are obtained for the PLA/LLDPE/LLDPE-g-AO/O-PCC composites variation of (69.5:19.5:10). :1) with a tensile strength of 22.629 MPa with a water absorption percentage of 45.36%. Keywords: PLA, LLDPE, LLDPE-g-AO, O-PCC, Glycerol